Cellular‐ and Subcellular‐Targeted Delivery Using a Simple All‐in‐One Polymeric Nanoassembly. (23rd October 2020) - Gao, Jingjing; Dutta, Kingshuk; Zhuang, Jiaming; Thayumanavan, S.
Abstract: Nanocarrier‐mediated drug delivery is a promising strategy to maximize the power of chemotherapy and minimize side effects. However, current approaches show insufficient drug‐loading capacity and inefficient drug release, and require complex modification processes. Attempts to enhance one of these features often compromise other merits. We describe here a block copolymer assembly system that combines desirable characteristics. The design of self‐immolative and crosslinkable hydrophobic moieties offer stable and high encapsulation. Redox‐triggerable polymer self‐immolation promotes drug release by switching the hydrophobic core into completely hydrophilic chains. The reactive amine handles, presented on their surface, allow "plug to direct" modification with targeting ligands. Functionalized nanoassemblies have been programmed to target specific subcellular compartments. The simplicity, versatility, and efficacy of the system open up possibilities for an all‐in‐one delivery system. Abstract : A block copolymer assembly system is reported for drug delivery. The hydrophobic core has a high drug capacity and is stabilized by disulfide linkages. Upon redox‐triggered cleavage of these disulfide linkages, the amphiphilic block polymer becomes hydrophilic, releasing the encapsulated drug. Reactive amine handles, presented on the nanocarrier surface, can be modified with targeting ligands to achieve cell‐ and organelle‐specific delivery.